2022
DOI: 10.5662/wjm.v12.i6.476
|View full text |Cite
|
Sign up to set email alerts
|

Associations between SARS-CoV-2 infections and thrombotic complications necessitating surgical intervention: A systematic review

Abstract: BACKGROUND Several unique clinical features of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the cause of coronavirus disease 2019 (COVID-19) infection, have been identified and characterized. One such feature, mostly among patients with severe COVID-19 infection, has become known as COVID-19-induced coagulopathy. Surgical patients with a history of or active COVID-19 infection bear a significantly higher risk for postoperative thrombotic complications. These patients may require s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Many studies have found COVID-19 to be associated with an increased risk of thrombosis, which is a key factor contributing to numerous complications of this infection (see reviews [37,38]). Having analyzed 20 studies enrolling 1,988 patients with COVID-19, Di Minno et al [39] calculated that the weighted mean prevalence of venous thromboembolism (VTE) was 31.3%, while deep vein thrombosis accounted for 19.8%, and pulmonary embolism -for 18.9%.…”
Section: Complications Of Covid-19mentioning
confidence: 99%
“…Many studies have found COVID-19 to be associated with an increased risk of thrombosis, which is a key factor contributing to numerous complications of this infection (see reviews [37,38]). Having analyzed 20 studies enrolling 1,988 patients with COVID-19, Di Minno et al [39] calculated that the weighted mean prevalence of venous thromboembolism (VTE) was 31.3%, while deep vein thrombosis accounted for 19.8%, and pulmonary embolism -for 18.9%.…”
Section: Complications Of Covid-19mentioning
confidence: 99%
“…Во многих исследованиях показано, что инфекция COVID-19 ассоциирована с повышенным риском тромбообразования -основным триггером многих осложнений этого заболевания (см. обзоры [37,38]). Например, Di Minno с соавт.…”
Section: осложненное течение Covid-19unclassified